Efektivitas telehealth nutrition counseling yang dipimpin perawat untuk pasien hemodialisis: Tinjauan sistematis - Nurrahmawati, Cici; Yulia, Yulia; Zahra, Anggri Noorana (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Hemodialysis is the main renal replacement therapy for end-stage chronic kidney disease, yet global dietary compliance among patients remains low (30–70%), including in Indonesia. Limited nutritional knowledge, entrenched eating habits, and inadequate access to counseling contribute to this problem. Nurse-led telehealth nutrition interventions supported by digital platforms have emerged as innovative strategies to enhance patient education and adherence.Objective: To review current evidence on the effectiveness of nurse-led, telehealth-based nutritional interventions in improving dietary compliance among hemodialysis patients.Methods: A systematic narrative review was conducted following PRISMA guidelines. Literature searches in Scopus, PubMed, and Google Scholar identified studies published between 2015 and 2025 using the keywords telehealth, nutrition counseling, and hemodialysis. Twelve out of ninety-five studies met the inclusion criteria: original research involving adult hemodialysis patients receiving nurse- or healthcare worker–delivered telehealth nutrition counseling. Data were synthesized narratively, and risk of bias was evaluated descriptively based on study design and reporting quality.Results: Most studies demonstrated significant improvements in nutritional knowledge, dietary compliance, and self-management (9/12 studies, p < 0.05). Effects on clinical outcomes such as hemoglobin, serum phosphate, and interdialytic weight were inconsistent, influenced by intervention duration, study design, and methodological quality. Telehealth approaches were feasible, acceptable, and beneficial in contexts with limited in-person care.Conclusion: Nurse-led telehealth nutritional interventions effectively improve dietary compliance and patient self-management in hemodialysis populations. Integration into primary and hospital-based care may strengthen continuity of care.